The geography of asset holdings: Evidence from Sweden - Nicolas Coeurdacier; Philippe Martin (Sveriges Riksbank, 2007)
This paper analyzes the determinants of cross-border asset holdings on cross-country data and a Swedish data set. We focus our analysis on the effect of the euro not only for the determinants of bond holdings, but also of equity and banking assets. With the help of a simple theoretical model, we attempt to disentangle the different effects that the euro may have had on asset holdings for both euro zone countries and countries outside of the euro zone such as Sweden. We find evidence that the euro has implied 1. a unilateral financial liberalization which makes it cheaper for all countries to buy euro zone assets. For bonds and equity holdings, this would translate into a 14% and 17% decrease in transaction costs. Using Swedish data, we find that the effect is larger for flows than for stocks. 2. a preferential financial liberalization which on top of the previous effect has decreased transaction costs inside the euro zone by 17% and 10% for bonds and equity respectively. 3. a diversion effect due to the fact that lower transaction costs inside the euro zone have led euro countries to purchase less Swedish equity. Our empirical analysis also suggests that the elasticity of substitution between bonds inside the euro zone is higher than between bonds denominated in different currencies. We illustrate this effect for transaction costs generated by the difference in the legal system.
Keywords: F30; F36; F41; G11; 330; International Asset Trade; Gravity Equation; Euro; Kapitalanlage; Anlageverhalten; Transaktionskosten; Vergleich; Euromarkt; Schweden